1974
DOI: 10.1159/000211997
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle and Organ Weights of Aged and Trained Male Rats

Abstract: Male rats of 90, 150, 300, 450 or 600 days of age were placed into sedentary or physical training experimental groups. Experimental animals ran daily for 20 min at 10–20 m/min on a treadmill set at an 8-degree incline. The experimental period lasted at least 300 days. Surviving rats from each group were chosen randomly and sacrificed at 150-day intervals up to 1,050 days of age. Muscle and organ weights were analyzed by grouping animals according to their age at death and also according to their age at the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…The decreased LV hypertrophic response in old rats is compatible with the results in a pressure overload experimental model previously reported by our laboratory (9). McCafferty and Edington (8) have reported that in animal models of exercise, the cardiac hypertrophic response in the senescent was less compared with the young adult animals. On the other hand, Florini et al (6) and Zitnik and Roth (7) have reported that hormonal stimulation (thyroid hormone) caused a similar extent of hypertrophy in old rats and old mice compared with young adult animals (6, 7).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The decreased LV hypertrophic response in old rats is compatible with the results in a pressure overload experimental model previously reported by our laboratory (9). McCafferty and Edington (8) have reported that in animal models of exercise, the cardiac hypertrophic response in the senescent was less compared with the young adult animals. On the other hand, Florini et al (6) and Zitnik and Roth (7) have reported that hormonal stimulation (thyroid hormone) caused a similar extent of hypertrophy in old rats and old mice compared with young adult animals (6, 7).…”
Section: Resultssupporting
confidence: 90%
“…Additionally, aging per se results in a modest increase in heart weights and in the size of individual myocytes in humans and animals (8,(12)(13)(14)(15)(16)(17). This age-associated change is functionally similar to that produced by pressure overload (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…1). The continued weight gain of this strain of Sprague-Dawley rat [Crl :COBSIaiCDIm(SD)] over the life span has been documented previously [29,12]. Table I contains mean values of the rates of oxidation catalyzed by gastrocnemius muscle homogenates from four groups of rats oxidizing six substrates in the presence of ADP.…”
Section: Body Weightmentioning
confidence: 99%
“…McCafferty and Edington (1974) also reported an increased heart weight with running in young and middle aged rats (90, 150, 300, and 450 days old). However, in old rats (600 days old) the exercised animals had lower heart weights than did the controls.…”
Section: -20mentioning
confidence: 82%